Pendidikan Agama Kristen sebagai Sarana Pengembangan Soft Skills Siswa - Agustin, Vera; Nurlatu, Eka; Tapilaha, Sandra Rosiana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christian Religious Education (CRE) not only functions as a means of delivering theological teachings, but also as a strategic medium in developing students' soft skills. This article aims to explore how Christian moral values ​​such as love, honesty, empathy, and justice can be integrated into learning practices to shape students' character and interpersonal skills. Through a qualitative-descriptive approach, this study collected data through observation, interviews, and documentation studies. The results show that PAK, through activities such as group discussions, social services, spiritual reflection, and project-based learning, contributes significantly to developing students' communication, leadership, cooperation, and emotional intelligence skills. The role of teachers as facilitators and moral role models is a key factor in the success of this process. Thus, PAK not only enriches the spiritual aspect, but also prepares students to become resilient and integral individuals in social life. The integration of faith values ​​with life skills is a strong foundation in forming a generation of Christians who are able to answer the challenges of the 21st century.